1987
DOI: 10.1152/ajpheart.1987.253.5.h1026
|View full text |Cite
|
Sign up to set email alerts
|

Sarcolemmal Na+-Ca2+ exchange activity in hearts subjected to hypoxia reoxygenation

Abstract: Although the occurrence of intracellular Ca2+ overload is known to be an important factor in hypoxia-reoxygenation injury, the exact mechanisms for this abnormality are not presently clear. Since Na+-Ca2+ exchange in the sarcolemmal membrane is considered to be involved in Ca2+ efflux, this study was undertaken to examine the effect of hypoxia reoxygenation on this system. Isolated rat hearts were made hypoxic by perfusing with a substrate-free medium gassed with 95% N2-5% CO2 and then reperfused with oxygenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The mechanism underlying the increase in NO production is not known. An increase in [Ca 2+ ] i under hypoxic conditions (Dixon et al 1987;Zhu and Nosek 1991) may serve as a second messenger to active NOS (Hampl et al 1995). Increases in NOS in pulmonary artery endothelium during hypoxia [4.9 kPa (about 38 mmHg)] were triggered by the initial transient increase in [Ca 2+ ] i (Hampl et al 1995).…”
Section: Effects Of No On Force Generation During Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism underlying the increase in NO production is not known. An increase in [Ca 2+ ] i under hypoxic conditions (Dixon et al 1987;Zhu and Nosek 1991) may serve as a second messenger to active NOS (Hampl et al 1995). Increases in NOS in pulmonary artery endothelium during hypoxia [4.9 kPa (about 38 mmHg)] were triggered by the initial transient increase in [Ca 2+ ] i (Hampl et al 1995).…”
Section: Effects Of No On Force Generation During Hypoxiamentioning
confidence: 99%
“…Hypoxia has been found to impair the re-uptake of Ca 2+ by the sarcoplasmic reticulum (SR) from the intracellular space (Dixon et al 1987;Zhu and Nosek 1991). This could result in an increase of intracellular Ca 2+ concentrations ([Ca 2+ ] i ), which, in turn, may potentiate NO production (Hampl et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that hypoxia directly affects NOS. Previous studies showed that hypoxia impairs the SR Ca 2ϩ reuptake from the intracellular space (12,52). This could result in an increase of [Ca 2ϩ ] i levels (52) and may, in turn, activate NOS via Ca 2ϩ -dependent NOS isoforms.…”
Section: Effects Of No On Isotonic Contractile and Fatigue Propertiesmentioning
confidence: 99%
“…Furthermore, the isotonic contractile properties better reflect diaphragm muscle performance in vivo (46). Hypoxia impairs the sarcoplasmic reticulum (SR) Ca 2ϩ reuptake from the intracellular space (12,52). This could result in an increase of intracellular Ca 2ϩ concentration levels ([Ca 2ϩ ] i ) and may, in turn, potentiate NO production by Ca 2ϩ -dependent NOS (19).…”
mentioning
confidence: 99%
“…Furthermore, Hata et al [84] showed that various types of oxygen free radical-generating systems inhibited the Na+-Ca 2+ exchange activity in sarcolemmal membrane vesicles isolated from rat, bovine, canine, and porcine hearts. Bersohn et al [ I 12], Daly et al [ 109], Meon et al [110], and Dixon et al [111,113] reported that heart sarcolemmal Na+-Ca 2 § exchange activity was depressed in hearts subjected to ischemia-reperfusion or hypoxiareoxygenation, and that the reduced activity of Na+-Ca 2+ exchange in ischemia-reperfused hearts was prevented by the addition of free radical scavengers to the perfusate [ 113].…”
Section: Na+-ca 2+ Exchangementioning
confidence: 99%